Edukasi Partisipatif Keselamatan Transportasi Wisata Bahari bagi Operator Kapal dan Wisatawan di Kawasan Kepulauan Kota Makassar - Indriaty Wulansari (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The Makassar City Islands, particularly the Spermonde Archipelago, rely heavily on marine transportation to support tourism activities. The increasing number of tourist visits has not been accompanied by adequate safety literacy, as reflected in the limited understanding of boat operators and tourists regarding maritime safety procedures, the inconsistent use of safety equipment, and the lack of continuous safety education. This community service program aimed to strengthen maritime tourism transportation safety literacy through a participatory educational approach integrating conceptual learning, interactive discussions, and practical safety simulations. The program involved 57 participants consisting of boat operators, tourism awareness groups, domestic tourists, and local government representatives. Program effectiveness was evaluated using pre-tests, post-tests, observations, and participant feedback. The findings revealed a 50% increase in participants' knowledge of maritime safety principles, safety equipment utilization, and emergency response procedures. Observations also indicated improvements in participants' practical skills, safety awareness, and engagement throughout the learning process. Beyond enhancing individual capacity, the program fostered stakeholder collaboration to support the development of a sustainable safety culture in marine tourism transportation across the Makassar City Islands.